Teamship Competance (Kompetensi Kolektif/Kolaborasi) - M. Resa Syah Pahlevi; Arifatul Amalia Febrianti; Moch Isa Ansori (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Each individual has characteristics and abilities that are inherent in each individual as the fundamental factors that make him different from other people. These characteristics and abilities are closely related to the effectiveness of each individual's performance which can be seen from behavior, way of thinking, acting style, and socializing.